Developing a classification system of social communication functioning of preschool children with autism spectrum disorder. (17th May 2016) - Di Rezze, Briano; Rosenbaum, Peter; Zwaigenbaum, Lonnie; Hidecker, Mary Jo Cooley; Stratford, Paul; Cousins, Martha; Camden, Chantal; Law, Mary
Abstract : Aim: Impairments in social communication are the hallmark of autism spectrum disorder (ASD). Operationalizing 'severity' in ASD has been challenging; thus, stratifying by functioning has not been possible. The purpose of this study is to describe the development of the Autism Classification System of Functioning: Social Communication (ACSF:SC) and to evaluate its consistency within and between parent and professional ratings. Method: (1) ACSF:SC development based on focus groups and surveys involving parents, educators, and clinicians familiar with preschoolers with ASD; and (2) evaluation of the intra‐ and interrater agreement of the ACSF:SC using weighted kappa ( к w ). Results: Seventy‐six participants were involved in the development process. Core characteristics of social communication were ascertained: communicative intent; communicative skills and reciprocity; and impact of environment. Five ACSF:SC levels were created and content‐validated across participants. Best capacity and typical performance agreement ratings varied as follows: intrarater agreement on 41 children was к w =0.61 to 0.69 for parents, and к w =0.71 to 0.95 for professionals; interrater agreement between professionals was к w =0.47 to 0.61, and between parents and professionals was к w =0.33 to 0.53. Interpretation: Perspectives from parents and professionals informed ACSF:SC development, providing common descriptions of the levels of everyday communicative abilities of children with ASD to complement the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition. Rater agreement demonstrates that the ACSF:SC can be used with acceptable consistency compared with other functional classification systems. What this paper adds: The Autism Classification System of Functioning: Social Communication (ACSF:SC) is an ICF‐based classification of autism spectrum disorder (ASD), social communication capacity, and typical performance. ACSF:SC provides a common language to classify what children can do. Early evidence demonstrates consistent ratings by parents and professionals. ACSF:SC provides a framework to develop additional ASD function‐based classification systems. This article is commented on by de Vries and Bölte on pages894–895 of this issue.